Digital image interpolation in Matlab - Kok, Chi-Wah (IEEE Press, 2019)
"Provides a comprehensive explanation of digital image interpolation - Logical and well-planned organization with easy to follow examples - An excellent reference for all digital image processing courses, in both computer science and electrical and computer engineering departments - Accompanying website includes Matlab source code to assist better learning and understanding of the algorithms Market description (Please include secondary markets) Tier C/P&R Primary: Researchers and engineers working in digital image and digital video Secondary: Graduate students studying digital image processing"--